Tantangan dan Strategi Muhammadiyah dalam Menghadapi Perkembangan Ilmu Pendidikan di Era Digital - Syaiful Bahri; Tabah Saefuloh; Nur Fauziah; Rizky Nur Lalita Firdaus; Astika Nurul Hidayah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This article examines Muhammadiyah's challenges and strategies in facing the development of educational science in the digital era. Using a normative research approach, this article explores Muhammadiyah's views regarding the influence of technology in education, as well as its application to Islamic values. Research findings show that the main challenges include the influence of globalization, developments in information technology, and the need for curriculum updates. As a solution, Muhammadiyah adopted an innovation-based strategy, such as developing digital learning models and technology training for educators. This research provides a strategic way for Muhammadiyah to strengthen its role as a main actor in modern Islamic education